Saccadic Eye Movements Attenuate Postural Sway but Less in Sleep-Deprived Young Adults - Ivan E. Pinto Vargas; Lucas E. Bicalho; Sérgio T. Rodrigues; José A. Barela (Frontiers Media S.A., 2020)
Sleep deprivation affects the performance of postural control and several other aspects related to attentional mechanisms that may alter sensory cue acquisition strategies. This study aimed to examine the possible effects of horizontal saccades and ocular fixation on a target in the performance of postural control in young adults with sleep deprivation. Twenty-six adults formed two groups, tested in two evaluations. In the first evaluation, participants slept normally on the night before. In the second evaluation, 13 participants were sleep deprived (SD) and 13 slept normally (control group [CG]) on the night before. In both evaluations, each participant stood upright as still as possible, in two experimental conditions: fixating the eye on a target and performing saccadic movement toward a target presented in two different locations (0.5 Hz). Each participant performed 3 trials in each condition, lasting 62 s each. Body oscillation was obtained in both anterior-posterior and medial-lateral directions. Results showed that SD participants swayed with a larger magnitude and higher velocity after sleep deprivation in the fixation condition. In the saccadic condition, body sway magnitude and velocity were reduced but were still larger/higher in the SD participants. Sleep deprivation deteriorates the performance of postural control. Saccadic eye movements improve postural control performance even in sleep-deprived participants but are still not sufficient to avoid postural control deterioration due to sleep deprivation.